(untitled) - Kovner, Anthony R. (New York, 1999)
This is the textbook of choice for an overview of the US health care system. The contributors address emergent and recurring issues -- such as national and local health care reform, primary prevention, Healthy People 2000, alternative medicine, multicultural issues, hospital organization, OBRA, DSM-IV, ethics, physician-assisted suicide -- with a complete public health and health policy perspective.The sixth edition is fully updated, comprehensive, and classroom user-friendly. Each chapter now includes learning objectives, a topical outline, a list of key terms, and mini-case studies for further discussion.
Keywords: Medical care,Chăm sóc y tế; United States,Hoa Kỳ